Impact of Public Sector Bank Merger Good And Bad on Indian Economics - Kumar Gupta, Dr Pradeep (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Development is the substance by which everyone pursues the normal life of the entrepreneur or someone. To achieve this substance, existing organizations go to reorganization taking advantage of the advantages and overcoming the disadvantages. In today's business world, mergers and acquisitions are spreading across industries that have carved a complete niche throughout the marketplace. Mergers and acquisitions are a normal way of life in the business world. In today's global competitive environment, mergers and acquisitions are the only key to long-term survival. They are a huge part of the world of corporate finance. The company's profits in India have increased by an average of 20-25% in the last 4 years as the company is an effective M&A strategy. This document presents its impact on GDP, profitability, employment and the general growth of the economy. There are different types of mergers and acquisitions in companies in the Indian economy, which may choose to reorganize them. This document also reflects recent cases of mergers and acquisitions and the reasons why companies choose this option. We also discuss the issues M&A companies face in the process and how to overcome these issues. Keywords: Corporate restructuring, Expansion, Mergers and acquisitions, Restructuring.